INTERTEKSTUAL DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI DENGAN NOVEL SANG PEMIMPI KARYA ANDREA HIRATA - Herna Yuanita Yuanita; Abdul Jalil Jalil; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research explains about intertextual in Negeri 5 Menara Novel by Ahmad Fuadi with Sang Pemimpi Novel by Andrea Hirata. The research aims to comparing the intertextual relationship in themes, event and characterization. The research uses qualitative approach and descriptive method that aims at describing the intertextual relationship contained in this novels. Theresult of this study also as a from of intertextual relationship documentation which is contained in Negeri 5 Menara Novel by Ahmad Fuadi with Sang Pemimpi Novel by Andrea Hirata. The research data was obtained by using techniques ofdocumentation and lirature. Based on the data analysis, it was known that both novel has the same main theme. Event and characterization contained both novel has similiarity and difference. Keywords: Intertextual, Theme, Event, Characterization, Negeri 5 Menara, Sang Pemimpi.